INJURIES INCIDENCE IN HANDBALL`S ATHLETES (Fiep Bulletin - online, 2014)
This quantitative descriptive study of diagnosis type aimed to investigate the academically handball athlete's injuries profile. Participated in this study nine players with an average of 22,2±1,4 year-old and practice time of 7,1±2,7 years. As measure instrument was used a questionnaire validated for this purpose, with 93% of validity and 100% of clarity. The data were treated with descriptive statistics (average, standard deviation, variation coefficient and simple frequency) and a Pearson`s correlation (p= 0,05). The results point that the injuries` attacked places were knee (5/12), following the ankle (3/12), shoulder (2/12), thigh (1/12) and foot (1/12). Relating to the injuries type, the most mentioned were twist (3/12), fractures (3/12), distention (1/12), contracture (1/12) and gore (1/12). The most common injury mechanisms were the dribble (4/16), the mark (4/16), the movement`s repetitiveness (3/16), the throw (3/16), the warming-up (1/16) and the ground impact (1/16). Some athletes answered more than one alternative, what modified the totality of the frequencies. No relationship were found among injury number and practice`s time (rc=0,39;0,27) nor with the players' age (rc=0,46;0,18). In spite of being an amateur team, the data obtained by the athletes' observation pointed to the need of improvement in the physical training to give conditions to support the successive training and game loads during the athletic career and, consequently, to prevent injuries factor.
Keywords: handball; injuries; injuries cause